PARTICLE BOARD QUALITY FROM PALM FROND WASTE (ARENGA PINNATA) - Thamrin G.A.R.; Yuniarti; Kurdiansyah (Russian Journal of Agricultural and Socio-Economic Sciences)
The need for housing for the Indonesian population is increasing with the increase of the population, so it is very important to meet the community's need for housing. Particle board is an alternative artificial board that can be developed by utilizing the potential of waste in South Kalimantan, one of which is processing particleboard made from sugar palm fronds and cement adhesive. This research was conducted at the ULM Faculty of Forestry Workshop and Forest Products Technology Laboratory, and at the Banjarbaru Industrial Research and Standardization Center using the Completely Randomized Design (RAL) method. Sampling was carried out in 3 treatments and 3 repetitions, namely sugar palm fronds with the composition of the binding material and using assessments based on the SNI-03-2105-2006 BSN (2006) standard. The results of testing the physical properties of palm frond particle cement board showed that the average water content value was 7.38% - 8.96%, density with an average value of 1.14 g/cm3 - 1.19 g /cm3, and the average thickness expansion value is between 0.93% - 1.43%. The MoE test results were obtained with an average value between 5242.52 kgf/cm2 - 7513.56 kgf/cm2, and MoR with an average value obtained ranging from 9.45 kgf/cm2 - 11.68 kgf/cm2. Based on the results of diversity analysis, adhesive concentration has a significant effect on water content, while it has no significant effect on density, thickness expansion, MoE and MoR. Particleboard from sugar palm fronds can be used as a source of board for communities around wetlands. The development of particle boards from sugar palm fronds needs to be encouraged to emerge and develop by exploiting the potential that exists in the community.